1973
DOI: 10.1159/000127673
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and Fibrinogen Reactions in <i>Pseudomonas aeruginos</i><i>a</i> Exotoxin Shock

Abstract: The distribution of radioactively labelled platelets, fibrinogen and erythrocytes in blood and various organs was studied after one injection of Pseudomonas aeruginosa exotoxin in dogs. The blood pressure often immediately dropped but then rapidly returned to the control level. This so-called anaphylactoid phase was followed by a progressive shock accompanied by decreasing blood pressure. The platelets also immediately decreased in the blood and appeared in the lungs during this anaphylactoid phase. Immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…We have given consideration to the blood inclusion but by measuring the hemoglobin concentration in the tissue homogenate. Indeed, platelets have been shown to be entrapped by the lung after trauma [21], septic shock [22] and hemorrhagic shock [23], or during the in vitro pump perfusion of the lung [24] and acute respiratory failure [25][26][27]. The reported accumulation ofplatelets in the lung following the traumatic, septic and hemorrhagic shock was a slow process.…”
Section: Discussionmentioning
confidence: 99%
“…We have given consideration to the blood inclusion but by measuring the hemoglobin concentration in the tissue homogenate. Indeed, platelets have been shown to be entrapped by the lung after trauma [21], septic shock [22] and hemorrhagic shock [23], or during the in vitro pump perfusion of the lung [24] and acute respiratory failure [25][26][27]. The reported accumulation ofplatelets in the lung following the traumatic, septic and hemorrhagic shock was a slow process.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of Pseudomonas aeruginosa exotoxin A by P. V. Liu (10), a number of studies have been made that suggest that the exotoxin greatly contributes to the virulence of the organism in a variety of animal models and tissue culture systems (1,2,6,8,12,(18)(19)(20). Several years ago it was found that P. aeruginosa exotoxin A (11), hereafter referred to as PA-toxin, inhibits protein synthesis in tissue cultures in vitro (19) and in mouse organs in vivo (20).…”
mentioning
confidence: 99%
“…Platelets in the capillaries, however, have not been counted. Platelets have been shown to be entrapped by the lung after trauma [12,13], septic shock [14,15], hemorrhagic shock [16], and acute respiratory failure [17][18][19][20]. Although the pulmonary accumulation of platelets after trauma is reportedly a slow process, the entrapment of platelets after cervical dislocation could have been caused, in part, by associated tissue injury, resulting in the formation in the lung capillaries of microthrombi [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The amount of 5HT measured in the lung seemed too high to be attributed to localization in the former two cell types described above. On the other hand, platelets are known to be entrapped by the lung after trauma [12,13], septic shock [14,15], hemorrhagic shock [16] and acute respiratory failute [17][18][19][20]. It is very possible that the high level of 5HT observed in the lung was due to the accumulation of platelets in that organ, but the localization of 5HT in lung tissue has not been determined.…”
Section: Introductionmentioning
confidence: 99%